1992
DOI: 10.1182/blood.v80.3.688.688
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant glycosylated human interleukin-6 accelerates peripheral blood platelet count recovery in radiation-induced bone marrow depression in baboons

Abstract: This report was aimed at confirming the potential clinical use for a genetically engineered glycosylated human interleukin-6 (rhIL-6) in hematopoiesis. Its tolerance and efficacy were assessed on hematopoietic restoration after neutron radiation-induced bone marrow injury on baboons, which represent an adequate model of parallelism for studying hematology in the human. The particular neutron radiation absorption pattern in the body allows the preservation of underexposed bone marrow areas that mimics an autotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…The results of present study are in accordance with previous observations, which showed the ability of IL-6 to induce anaemia in different animal models and in humans [12,15]. Thus, a relationship between IL-6 and anaemia seems to be established.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of present study are in accordance with previous observations, which showed the ability of IL-6 to induce anaemia in different animal models and in humans [12,15]. Thus, a relationship between IL-6 and anaemia seems to be established.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, sequestration of erythrocytes was mentioned as a possible explanation for IL-6 induced anaemia [12,15], whereas previously a shortened life span of erythrocytes was postulated to be involved in ACD [29]. No evidence for enhanced elimination of erythrocytes, from the circulation to the liver, was found after i.p.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To summarize, in this study we have described a useful procedure for the large-scale production and the detailed chemical, physicochemical and functional characterization of a recombinant mutant IL-6. Sufficient amounts of a clinical-grade cytokine are now available for future structure/function studies and for investigating its therapeutic use, specifically in platelet recovery after radiotherapy, chemotherapy (Kimura et al, 1990 ;Carrington et al, 1992), and bone marrow transplantation (Herodin et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to detect activity in the serum and urine of thrombocytopenic animals that stimulated the growth of megakaryocytic progenitors in vitro, yet purification of thrombopoietin remained elusive. Factors that can promote the in vitro proliferation of megakaryocytic progenitor cells, and to a lesser extent, indirectly stimulate in vivo thrombocytopoiesis, have been identified, including IL-3 [35], IL-6 [36][37][38], IL-1 [35], IL-11 [39,40] and GM-CSF [41]. However, stimulation of the terminal differentiative events in steady-state thrombocytopoiesis does not appear to be a primary role for most of these factors, as experiments with knock-out mice have demonstrated [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%